2013
DOI: 10.1038/srep03490
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Li4Ti5O12/TiO2 composite tubes with regular structural imperfection for lithium ion storage

Abstract: Hierarchical Li4Ti5O12/TiO2 tubes composed of ultrathin nanoflakes have been successfully fabricated via the calcination of the hydrothermal product of a porous amorphous TiO2 precursor and lithium hydroxide monohydrate. The hierarchical tubes are characterized by powder X-ray diffraction, nitrogen adsorption/desorption, scanning electron microscopy and transmission electron microscopy techniques. These nanoflakes exhibit a quite complex submicroscopic structure with regular structural imperfection, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 32 publications
1
27
1
Order By: Relevance
“…It is worth noting that mixed phase has multiple advantages over pure phase likewise, high grain boundary Scheme 1 Schematic illustration of synthesis method for CoSn x @C-PAn via in-situ polymerization and annealing processes; further presenting the mechanism of lithium storage in the hybrid. densities enhance the interfacial Li + storage through space layer charge and thus offer large capacity and provide channels for faster transport of Li + in the NPs [34,35]. XRD pattern of CoSn x @C-PAn also shows two diffraction peaks at 26.61 and 51.71, attributed to (110) and (211) reflections of SnO 2 , respectively (JCPDS no.…”
Section: Resultsmentioning
confidence: 92%
“…It is worth noting that mixed phase has multiple advantages over pure phase likewise, high grain boundary Scheme 1 Schematic illustration of synthesis method for CoSn x @C-PAn via in-situ polymerization and annealing processes; further presenting the mechanism of lithium storage in the hybrid. densities enhance the interfacial Li + storage through space layer charge and thus offer large capacity and provide channels for faster transport of Li + in the NPs [34,35]. XRD pattern of CoSn x @C-PAn also shows two diffraction peaks at 26.61 and 51.71, attributed to (110) and (211) reflections of SnO 2 , respectively (JCPDS no.…”
Section: Resultsmentioning
confidence: 92%
“…In last five years, many groups have studied composites of Li 4 Ti 5 O 2 with metal oxides to explore high rate capability with rich grain boundaries enabling fast diffusion of ions into the active material. [27][28][29][30][31][32][33] In this regard, Li 4 Figure S1). Sintering the sample for 2 hours resulted into pure Li 4 prepared by grinding and sonicating 80 wt % of the sample to be examined, 10 wt % acetylene black and 10 wt % polyvinylidene flouride (PVDF) binder in N-methyl-pyrrolidinone solvent.…”
Section: Introductionmentioning
confidence: 99%
“…Several research results have been reported on hyperbranch designs developed to increase the specific surface area of metal oxide nanostructures [13][14][15][16][17]. However, the volume change occurring during the lithiationdelithiation process may still break the electrical contact pathways in metal oxide electrodes.…”
Section: Introductionmentioning
confidence: 97%